2000
DOI: 10.1046/j.1523-5378.2000.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori Eradication on Peptic Ulcer Disease Complicated with Outlet Obstruction

Abstract: We suggest that H. pylori eradication may improve the resolution in obstructive ulcer cases with colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…It is even suggested that Helicobacter pylori eradication may improve the resolution in obstructive ulcer cases with colonization [12].…”
Section: Discussionmentioning
confidence: 99%
“…It is even suggested that Helicobacter pylori eradication may improve the resolution in obstructive ulcer cases with colonization [12].…”
Section: Discussionmentioning
confidence: 99%
“…As with other complications, the rate of Hp infection in patients not consuming NSAIDs is controversial [360,361]. As with other complications, the rate of Hp infection in patients not consuming NSAIDs is controversial [360,361].…”
Section: Gastric Outlet Obstruction Pathophysiology and Epidemiologymentioning
confidence: 99%
“…This complication can be treated surgically or endoscopically [39, 51]. Although only scattered evidence exists in the current literature, it has been suggested that gastric outlet obstruction can be successfully treated with H. pylori eradication in positive patients [52, 53]. It should be kept in mind that eradication therapy is indicated in all H. pylori -positive patients undergoing surgical or endoscopic therapy for gastric outlet obstruction.…”
Section: Gastric Ulcer and Duodenal Ulcermentioning
confidence: 99%